Penurunan Angka Stunting Melalui Penyuluhan Pencegahan Stunting Desa Waru Demak - Mila, Zamilatul; Azizah, Rizky Annisa'; Rahmawati, Putri; Sa'adah, Naili; Sasgapata Kurniawan, Annugallakata Nea; Kharullah , Ilham; Kholifah , Umi; Shabrina , Nada Nasywa; Fahreza , Muhammad Nouval Raya; Agustina , Sofyya; Andriyani, Evita Ayu; Munashiva, Nur Shifiya; Wangi, Nabila Mega; Septian , Asya Ainu; Qoni'ah, Fadhilatul; Perdana , Fatkhi Zalfa (Yayasan Inspirasi El Burhani, 2025)
Introduction: Stunting remains a serious public health issue in Indonesia, particularly in rural areas. Objective: This community service activity aims to examine and analyze the development of stunting cases in Waru Village, Mranggen Subdistrict, Demak Regency. One of the main contributing factors to stunting is the lack of knowledge and self-confidence among mothers of toddlers, which leads many of them to avoid visiting the local health post (posyandu). Method: The approach used in this activity is the Participatory Action Research (PAR) method, involving observation, socialization, training on stunting and balanced nutrition, as well as facilitating two-way dialogue with posyandu cadres, midwives, and mothers of toddlers. Result: The results showed a decrease in stunting cases, marked by an increase in the mothers' self-confidence, knowledge, and awareness of the importance of proper nutrition and parenting practices. Conclusion: The success of this program shows that a direct, participatory, and diverse communication approach is able to provide education on nutrition and early prevention of stunting. Counseling that is carried out consistently and touches on various aspects of community life has proven effective in changing the mindset and behavior of parents, especially in terms of providing nutritional intake, monitoring child growth and development, and utilizing health services available in the village.